Feminism, Violence Against Women, and Law Reform : Decolonial Lessons From Ecuador - Silvana Tapia Tapia (New York Routledge, 2022)
School of Law, Governance and Public Policy
MIR No: 170
Keywords: Law, Society, Feminism, Violence